Comparison of experimental nerve injury caused by ultrasonically activated scalpel and electrosurgery - Carlander, J.; Johansson, K.; Lindström, S.; Velin, Å. K.; Jiang, C. H.; Nordborg, C. (British journal of surgery, 2005)
Background: Iatrogenic nerve injury caused by heat from dissection instruments is a significant problem in many areas of surgery. The aim of the present study was to compare the risk of nerve injury for three different dissection instruments: monopolar and bipolar electrosurgery (ES) and an ultrasonically activated (US) instrument. Methods: The biceps femoris muscle was cut in a standard manner just adjacent to the sciatic nerve using monopolar ES, bipolar ES or US shears. A total of 73 functional experiments were conducted in which the nerve was isolated, divided proximally, and stimulated supramaximally in 37 anaesthetized rats. The electromyographic (EMG) potential was recorded distally before and after each experiment. Nerve dysfunction was defined as more than 10 per cent loss of the evoked EMG potential. Fifty‐nine nerves were examined histologically after dissection with the different instruments. The extent of heat damage was determined in four nerves that were divided with ES bipolar scissors and five that were divided with US shears. Results: Reduction in the EMG potential was significantly more frequent in the monopolar ES group than in the US group. Morphological examination also showed significantly less nerve damage in the US group. Conclusion: US instruments may be safer than ES for dissection close to nerves. Copyright © 2005 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd. Ultrasound does less damage